High prevalence of MiTF staining in undifferentiated pleomorphic sarcoma: caution in the use of melanocytic markers in sarcoma. Issue 5 (1st February 2017) - Choy, Bonnie; Hyjek, Elizabeth; Montag, Anthony G; Pytel, Peter; Haydon, Rex; Luu, Hue H; Zhen, Chao J; Long, Bradley C; Kadri, Sabah; Segal, Jeremy P; Furtado, Larissa V; Cipriani, Nicole A
Abstract : Aims: The diagnosis of undifferentiated pleomorphic sarcoma (UPS) may be challenging, as other lesions with undifferentiated spindle cell morphology must be excluded, including melanoma. Microphthalmia‐associated transcription factor (MiTF) stains naevi and epithelioid melanomas, as well as some mesenchymal neoplasms. The aim of this study was to evaluate the prevalence of MiTF and melanocytic markers in UPS and a subset of atypical fibroxanthoma (AFX). Methods and results: MiTF, SOX10, Melan‐A, HMB45 and S100 immunostaining was performed on resection specimens from 19 UPSs and five AFXs. Next‐generation sequencing of 50 genes was performed in UPSs to exclude dedifferentiated melanoma. In 17 of 19 UPSs (89%), tumour cells showed nuclear positivity for MiTF that was not eliminated by casein block. Three showed focal nuclear staining for HMB45, which was eliminated by casein block. One showed focal nuclear vacuole staining for S100 with red but not brown chromogen. None expressed SOX10 or Melan‐A. Mutational analysis of 15 UPSs with adequate DNA showed no mutations within hotspot regions of BRAF, KIT, or NRAS . Four of five AFXs (80%) stained with MiTF; other markers were negative. Conclusion: There is a high prevalence of nuclear MiTF expression in UPSs (89%) and AFXs (80%). Rare UPSs showed non‐specific nuclear HMB45 or S100 staining. These findings argue against using MiTF in isolation to differentiate between UPS or AFX and melanoma, and caution in interpreting focal staining for a single additional melanocytic marker. Casein block may eliminate non‐specific staining. MiTF should be used to support a diagnosis of melanoma only if multiple melanocytic markers are positive.